Challenges faced by intermediate phase isiZulu teachers in teaching inclusive reading - Ntshangase, Chief (Journal for Language Teaching, 2023)
Despite several interventions put in place to alleviate the reading crisis in South African education, many teachers still experience challenges in teaching reading comprehension. The situation is even more dire with regards to teaching inclusive reading to at-risk readers in mainstream schools in under-resourced settings. Very few studies have been conducted to investigate the pedagogical strategies in teaching inclusive reading in the intermediate phase (IP) isiZulu classrooms. This study aims to investigate the pedagogical challenges faced by IP isiZulu teachers who are teaching reading comprehension skills to at-risk readers in the mainstream schools of uMkhanyakude district, in the Northern part of KwaZulu-Natal province. This qualitative study is guided by the Word Learning Theory which posits that reading instruction should enhance learners’ knowledge of the alphabet and high-frequency words. Data were collected through non-participant classroom observations and interviews with 10 IP isiZulu teachers based in uMkhanyakude district. The qualitative data were analysed by the researcher through coded thematic analysis. The units of analysis in this study are IP teachers’ pedagogic strategies in teaching inclusive reading. The findings indicate that IP isiZulu teachers struggle to organise meaningful and cohesive reading strategies. Strategies employed are not structured to address specific reading challenges and consequently at-risk readers in mainstream schools remain inadequately catered for. This study will contribute to the body of knowledge related to the pedagogical strategies best suited for developing inclusive reading.